Introducing Tlhalosi ya Medi ya Setswana: The Design and Compilation of a Monolingual Setswana Dictionary - Otlogetswe, Thapelo J. (Lexikos, 2013)
This paper presents the design elements of a recently published monolingual Setswana dictionary, Tlhalosi ya Medi ya Setswana (Otlogetswe 2012), the fourth main Setswana monolingual dictionary to appear. The paper situates the dictionary within a recent, but growing Setswana monolingual dictionary tradition whose roots may be traced to 1976 when M.L.A. Kgasa's Thanodi ya Setswana ya Dikole was published. However, before this date, the development of Setswana lexicography lies wholly in a bilingual dictionary tradition which dates back to the 1800s. The paper also discusses the different features of Tlhalosi ya Medi ya Setswana demonstrating that it possesses some dictionary features which are not found in previous Setswana dictionaries such as frequency information, phonemic transcription and extensive cross-referencing.